An Overview on Agriculture Management (International Journal of Innovative Research in Engineering & Management, 2021)
Agriculture has been performed as a life-sustaining activity in  every nation in the globe from ancient times, when other  development sectors did not even exist. In the case of India, it  was a net importer of food grains in the early 1960s before  becoming an exporter of a variety of agricultural goods.  Marketing and development have become buzzwords in the  agricultural sector as a consequence of globalization's  impacts; biotechnology, precision farming, and the  employment of different highly automated methods have also  contributed to a paradigm shift in the area of agriculture.  Aside from the government's exclusive emphasis on  privatization, farmer organizations, public-private  partnerships, and entrepreneurs have all turned their attention  to agricultural development. Furthermore, the participation of  erudite people has been critical in attaining progress in the  agricultural industry. The agricultural situation has improved  with the introduction of chemical manures, new and better  plant varieties, and reduced reliance on climatic conditions  owing to technical progress. As a consequence, agriculture  has evolved into a synthesis of science, business, and  commerce.
Keywords: Agriculture; Crop; Farmer; Harvest; Management; Soil